O ÔNUS DA PROVA E A TEORIA DAS CARGAS PROBATÓRIAS DINÂMICAS NO PROCESSO ADMINISTRATIVO TRIBUTÁRIO: UMA ANÁLISE À LUZ DO ART. 373, § 1º DO CÓDIGO DE PROCESSO CIVIL DE 2015 - Rosa, Andre Luiz Figueiredo (2020)
The problem of the procedural burden of proof has aroused doctrinal debates for a long time, especially the isonomy criterion and the fundamental guarantee of the fair and adequate provision of tutelage under material law. At the beginning of the 19th cen